Allosteric Antagonism of the A2A Adenosine Receptor by a Series of Bitopic Ligands - Zhan-Guo Gao; Kiran S. Toti; Ryan Campbell; R. Rama Suresh; Huijun Yang; Kenneth A. Jacobson (Cells, 2020)
Allosteric antagonism by bitopic ligands, as reported for many receptors, is a distinct modulatory mechanism. Although several bitopic A2A adenosine receptor (A2AAR) ligand classes were reported as pharmacological tools, their receptor binding and functional antagonism patterns, i.e., allosteric or competitive, were not well characterized. Therefore, here we systematically characterized A2AAR binding and functional antagonism of two distinct antagonist chemical classes. i.e., fluorescent conjugates of xanthine amine congener (XAC) and SCH442416. Bitopic ligands were potent, weak, competitive or allosteric, based on the combination of pharmacophore, linker and fluorophore. Among antagonists tested, XAC, XAC245, XAC488, SCH442416, MRS7352 showed Ki binding values consistent with KB values from functional antagonism. Interestingly, MRS7396, XAC-X-BY630 (XAC630) and 5-(N,N-hexamethylene)amiloride (HMA) were 9–100 times weaker in displacing fluorescent MRS7416 binding than radioligand binding. XAC245, XAC630, MRS7396, MRS7416 and MRS7322 behaved as allosteric A2AAR antagonists, whereas XAC488 and MRS7395 antagonized competitively. Schild analysis showed antagonism slopes of 0.42 and 0.47 for MRS7396 and XAC630, respectively. Allosteric antagonists HMA and MRS7396 were more potent in displacing [3H]ZM241385 binding than MRS7416 binding. Sodium site D52N mutation increased and decreased affinity of HMA and MRS7396, respectively, suggesting possible preference for different A2AAR conformations. The allosteric binding properties of some bitopic ligands were rationalized and analyzed using the Hall two-state allosteric model. Thus, fluorophore tethering to an orthosteric ligand is not neutral pharmacologically and may confer unexpected properties to the conjugate.